Characteristics and Triggering Conditions for Naturally Deposited Gravelly Soils that Liquefied following the 2008 Wenchuan Mw 7.9 Earthquake, China. Issue 3 (August 2018) - Chen, Longwei; Yuan, Xiaoming; Cao, Zhenzhong; Sun, Rui; Wang, Weiming; Liu, Huida
The 2008 Mw 7.9 Wenchuan, earthquake caused naturally deposited ravelly soils to liquefy over a wide area. Although liquefaction of gravely soils is recognized by the geotechnical profession, observations of liquefaction and nonlique-faction case histories within the literature are few. Through several years of systematic study following the 2008 Wenchuan earthquake (Mw 7.9), 92 locations of gravel liquefaction were identified, described, and mapped. These locations lie within an approximately 3, 000 km 2 area of the Chengdu Plain. Peak ground accelerations estimated at the sites range from 0.15 g to 0.49 g. Taken collectively, these studies reveal the necessary conditions for liquefaction triggering in gravelly materials. Grain size analyses indicates that the ejecta was much finer than the gravels that liquefied. Gravel contents of liquefied soils ranged from 5% to more than 85%. The liquefied gravelly soils were loose, but their measured shear wave velocities range from 133 m/s to 267 m/s, with corrected values ranging from 154 m/s to 31 4m/s. The unique depositional conditions under Chengdu Plain provide favorable conditions for extensive liquefaction of gravelly soils. The shallow soil profiles consist of a 0.5 m to 5.5 m impermeable soil (i.e., the capping layer) overlying gravels ranging in thickness from a few meters to hundreds of meters.